Corporate Accountability In Crime of Licensing By Law Number 10 of 1998 On Banking - Bastianto Nugroho; Sumarso . (Yurisdiksi: Jurnal Wacana Hukum dan Sains, 2017)
Corporate development  as development  actors increas ingly play an important  role in people's lives . Therefo re doubts in the pas t to place the corporation as a s ubject of criminal la w to co mmit criminal acts  and accountable  in criminal  law, has now s hifted. T he doctrine of non potestdelinquere university (the  corporation   may  co mmit  a  c riminal  offens e)began  to  be  abandoned  by  accepting  corporate res pons ibility as a ma ker o f criminal offens es in addition to the natural man. Determination of corporate res pons ibility as a ma ker of criminal offens es in the criminal law s ee ms to have become demands of the times who could not be ignored to improve the state's res pons ibility to manage our increas ingly comple x s ociety, as it appears in the manus cript draft Penal Code wh ich have reached the s tage of receiving and formulat ing the corporation as s ubject follow criminal and criminally res pons ible. Pole mics appear along es pous ed  corporate  respons ibility   in  crimina l  law.  For  that  planning   mus t  include  planning  and enforcement a imed at provid ing legal protection for people agains t la wles s nes s and crime. Als o keep in mind  that the development  of society  and  modernization  brings  great  influence  in the  makeup  of the community  was included  in the law.This  res earch us e method approach of law(statuteapproach) and the conceptual  approach (conceptualapproach).Approach  legis lation(statuteapproach) that s olve the s olution of  the  question  by  relying  on  the  provis ions  of  the  legis lation  and  regulations  relevant  conceptual approach(conceptualapproach)that   s olves  the  ans wers  to  the  formulat ion  of  the  proble m pos ed  by referring to the concep t of legal principles re levant.